Mullerian Inhibiting Substance acts as a motor neuron survival factor in vitro - Wang, Pei-Yu (National Academy of Sciences, 2005)
The survival of motor neurons is controlled by multiple factors that regulate different aspects of their physiology. The identification of these factors is important because of their relationship to motor neuron disease. We investigate here whether Mullerian Inhibiting Substance (MIS) is a motor neuron survival factor. We find that motor neurons from adult mice synthesize MIS and express its receptors, suggesting that mature motor neurons use MIS in an autocrine fashion or as a way to communicate with each other. MIS was observed to support the survival and differentiation of embryonic motor neurons in vitro. During development, male-specific MIS may have a hormone effect because the blood-brain barrier has yet to form, raising the possibility that MIS participates in generating sex-specific differences in motor neurons.